Potentiality of Periphyton-based Aquaculture Technology in Rice-fish Environment (Journal of Scientific Research, 2009)
Periphyton is being used traditionally as rich aquatic feed for fishes throughout the countries like Cambodia, West Africa, Srilanka, India and Bangladesh. In waterlogged rice environment, it can be judiciously utilized as feed source introducing periphytophagous fish. Studies supported rice straw as suitable substrate for periphyton growth. The study of gut content of Common carp (Cyprinus carpio L.) from a periphyton-based rice-fish culture system in Apatani Plateau of Arunachal Pradesh, India showed maximum of 60 genera of microflora and fauna with periphytic in nature. The farmers from this rice-fish culture practice are gaining an average fish production of 500kg ha-1 180 day-1 without employing any supplementary feed. Better selection and determination of appropriate stocking density of periphytophagous fish in waterlogged rice-fields might extend the rice-fish culture towards a sustainable and self-substrating periphyton based aquaculture (SSPBA) practice. Keywords: Periphyton; Sustainable agriculture; Rice-fish; Self-substrating; Common carp; Apatani plateau. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2114              J. Sci. Res. 1 (3), 624-634 (2009)